(untitled) (Bangladesh Journal of Medicine, 2025)
Background: Aging is a natural physiological process that affects various organs, including the skin. The elderly population in Bangladesh is rapidly increasing, necessitating an understanding of the common skin diseases affecting this demographic. The aim was to investigate the frequency, patterns, and associated factors of skin diseases among elderly patients attending a tertiary care center in Bangladesh. Methods: This cross-sectional survey was conducted during January 2024 to April-2024, at the department of Dermatology & Venereology in Mugda Medical College Hospital, Dhaka, Bangladesh. A total of 233 elderly patients aged 60 years and above were enrolled using consecutive sampling technique. Data were collected using a structured questionnaire capturing demographics, clinical presentations, and comorbidities, followed by clinical examinations. The data were analyzed using Statistical Package for Social Sciences (SPSS), version-23.0. Results: The mean age of the study patients was 65.64±5.54 years, with a nearly balanced gender distribution (48.92% male, 51.07% female). Common clinical presentations included itching (84.12%), redness (14.16%), and blistering (3%). Plaques (51.07%) and papules (46.35%) were the most frequent primary lesions, while scaling (53.21%) and erosion (36.05%) were common secondary lesions. Non-infectious skin diseases were more prevalent (58.79%) than infectious diseases (41.2%), with dermatitis (37.76%) and fungal infections (21.03%) being the most frequent conditions. A significant association was observed between educational level and infectious skin diseases with the study patients (p=0.001), with fungal infections more common among no formally educated patients. Similarly, diabetic-non- diabetic cases showed a significant association with infectious-non-infectious skin diseases (p=0.001). Conclusion: Skin diseases in elderly population can present with diverse clinical picture where dermatitis and fungal skin infections are more common. Patient’s educational status and comorbidities may play a role in acquiring particular illnesses. Bangladesh J Medicine 2025; 36(2): 130-135